A Review on (Dalbergia Sissoo Roxb.) with special reference to its Role in Kustha as Per Brihtrayi - kumari, Pramila; sharma, Ashwini Kumar; soni, Pradeep; Masum (International Research Journal of Ayurveda & Yoga, 2022)
From the very first time man has been in close contact with the flora around him. From time passing directed him to use different plants to treat various ailments. The analysis of Dravya. Rasa, Guna, Virya and Vipaka on the basis of Panchamahabhut is a remarkable landmark during samhita period and classical uses are also important. There are many drugs were in practical use and the data’s recorded in the form of samhita. The present encyclopaedic study aims to high lighten the therapeutic value of Simsapa (Dalbergia sissoo Roxb.) with special reference in kustha. Dalbergia sissoo(Roxb.) is one of the important plant species used for Kustha.